EKSPLORASI ETNOMATEMATIKA DALAM MOTIF BATIK KHAS BANYUWANGI - Prabowo, Akbar (SIGMA, 2024)
The purpose of this study is to describe the mathematical concepts found in traditional Banyuwangi batik and how they can be utilized in mathematics education. This research employs a qualitative descriptive method with an ethnographic approach. The instrument for this study is the human instrument, wherein the researcher directly participates in data collection through observation, interviews, and documentation. The data analysis process includes data reduction, data presentation, and data interpretation. The results of this study reveal that there are transformation geometry concepts found in the unique motifs of Banyuwangi batik, including translation, reflection, rotation, and dilation. These mathematical concepts are identified in several distinctive Banyuwangi batik patterns, such as batik kopi pecah, gajah oling, blarak sempal, and manuk kecaruk. The mathematical concepts discovered in these unique Banyuwangi batik motifs can be used to introduce and understand mathematical concepts through local culture.